The relationship between lyrics and melody in Rimi vocal music - Olson, Howard S. (International Library of African Music, 1980)
This article on Rimi vocal music is written with two purposes in mind: 1) to introduce the reader to Rimi music, and 2) to demonstrate the correlation between a tonal language and vocal music. To achieve this goal a very simple finger counting song has been chosen for analysis. A study of Rimi vocal music was made in conjunction with the author’s linguistic analysis of the language. Since culture is a whole, and music is associated with so many aspects of the culture, linguistic research, of necessity, entailed an examination of Rjmi music. It was found that a knowledge of vocal music gave clues and corroboration to the tonal analysis of the language. Moreover, the study of the lyrics revealed many helpful examples of vowel coalescence.
Keywords: African Music